Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1287/isre.1120.0468
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Examination of the Antecedents and Consequences of Contribution Patterns in Crowd-Funded Markets

Abstract: Management, as well as seminar participants at the Fox School of Business at Temple University for useful suggestions. They also thank Ashish Agarwal, Avi Goldfarb, Yili Hong, Pei-yu Chen and Evan Polman for providing helpful comments. Anindya Ghose acknowledges funding from the WCAI (Wharton Customer Analytics Institute) and NSF CAREER Award IIS-0643847.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
414
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 648 publications
(435 citation statements)
references
References 66 publications
13
414
1
7
Order By: Relevance
“…Another research stream concentrates on factors that influence funders' decision process and contribution patterns such as funders' cultural and geographic differences [1][17] [45], desire for social interactions with those who are involved in to the project [33] and funders' altruism [16]. The majority of the studies in the latter research stream focus on herd behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Another research stream concentrates on factors that influence funders' decision process and contribution patterns such as funders' cultural and geographic differences [1][17] [45], desire for social interactions with those who are involved in to the project [33] and funders' altruism [16]. The majority of the studies in the latter research stream focus on herd behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have found support for this herd behavior [9][12] [36] [44]. However, further evidence shows that this herd behavior leads to negative externalities in the form of suboptimal decisions [16] [56]. Risky or bad projects are still funded since funders make decisions not based on the characteristics of the project or its initiator but based on the number of people who have invested before them.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, individuals would decrease their contributions when others have already contributed more to a project and turn to other projects with less success [6]. This is because the crowds participant in donation-based crowdfunding platforms for the purpose of helping others without tangible or financial rewards [6,29].…”
Section: Funds Pledgementioning
confidence: 99%
“…For project fundraisers, they acquire disperse resources (i.e., money) from different crowds, which is manifested on the crowdfunding platforms through the participation or contribution behaviors of different crowds [6]. On a crowdfunding platform, there are three ways for crowds to participate: (1) funds pledge, (2) popularity creation (i.e., clicking like), and (3) on-site communication (i.e., interaction between the crowds and fundraisers).…”
Section: Introductionmentioning
confidence: 99%